Analysis on Health Level of Local Government Owned Enterprises (BUMD) toward Papua Regional Income - Yohanis Rante; Westim Ratang; B. Elita Bharanti (Journal of Social and Development Sciences, 2016)
In the effort to carry out the principal functions and duties for the population in Papua, Papua provincial government set up several enterprises (BUMD) purposed to provide services to the public. BUMD is also expected to give contribution on regional income. The objectives of this research are: (1) Determining the health level of Local Government Owned Enterprises in Water Supply Company in Jayapura and Nabire from the financial aspect, (2) the health level of Local Government Owned Enterprises in Water Supply Company in Jayapura from the operational aspect, (3) the health level of Local Government Owned Enterprises in Water Supply Company in Jayapura and Nabire from the administration aspect. The method used in this research is survey research method toward BUMD by distributing questionnaires in several enterprises. The analytical tool used is the analysis on the health level of Water Supply Company on the financial, operational and administration aspects. Jayapura Water Supply Company health level in terms of financial aspects, operations and administration in 2011 to 2013 showed a reduction, but it was still sufficient indication. The total value of these three aspects has decreased in the last two years, 60.49 in 2011, decrease to 59.22 in 2012 and 54.59 by the end of 2013. However, this reduction was still at fairly healthcategory. Nabire Water Supply Company health level based on the financial aspect shows that from 2010 to 2013, the financial performance of Nabire Water Supply Company was experiencing unhealthy condition. Service aspect of the rate of complaints solving in 2010 to 2013 was always above 100%, it means that Nabire Water Supply Company have solved the problem of water services and other complaints that come from customers or not customer. The next indicator is water quality was 0% from 2010 to 2013. It means that they have not been able to serve the customers with the drinking water quality as provided in Ministry of Health Regulationnumber 492/MENKES/PER/IV/ 2010.